Gnojišča na Ljubljanskem polju - Kladnik, Drago (Georitem, 2008)
The extensive groundwater reserves in the Ljubljana Plain, estimated at 100 million m3, represent a natural resource of regional significance. The Decree on the Protection of Sources of Drinking Water divides this water protection area into three drinking-water protection zones. The area is exposed to possible pollution by many activities, among which agriculture is especially problematic because it is not supervised strictly enough. The majority of farms are engaged in traditional animal husbandry, of which cattle breeding dominates.